ISPC Commentary on the Proposal for CRP3.3 - July 2010 - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2010)
Initial comments from the interim Independent Science and Partnership Council on the proposal for CRP 3.3: GRiSP, Global Rice Science Partnership - the first fast tracked CGIAR Mega Program proposal.